Notes on Loving a Mourner (with Roland Barthes and Others). Issue 2 (July 2017) - Phillips, Matt
Abstract : This essay examines the place of love in grief, staging a relation between a mourner and her lover. Taking as its point of departure Freud's observation that mourning leads to a 'loss of the capacity to love', it considers the effects bereavement might have on the bereaved's relations with those that love them, and the possibilities, pitfalls and ethics of care in such a context. This is explored largely through a reading of Roland Barthes's late work (both as a writer of grief and a theorist of love), as well as ideas drawn from Sigmund Freud, Melanie Klein, Sara Ahmed, Hamlet and personal observation. Love and care are thought through alongside notions of 'tact', 'benevolence' and 'parrying against reduction' in late Barthes.